Project Evaluation Methodology and Software Tool for Innovation Contests - Vargas Pérez, Laura Silvia; Soto Hernandez, Ana Maria; Felipe Riverón, Edgardo Manuel; Camero Berrones, Rosa Gabriela; Sanchez Hernandez, Zoila Erika; Vargas Pérez, Vanessa Atenea (LACCEI, 2023)
Abstract- In this research, job results are oriented to help organizational entities that need to select easily from a group, those projects developed with the highest quality. In addition, this system provides support and in project competitions authors establishes impartiality and the possible greater numerical accuracy. This paper proposes a methodology to evaluate innovation, creativity, and quality in a project competition, to determine the best ones. Authors implement them through a software application including a qualimetric model. This assists evaluators in determining, with the greatest numerical accuracy possible, the outcome of the competition. Finally, authors give some practical guidelines to concrete a correct instrumentation of the evaluation procedures, such as ranking, presentation and documentation. Keywords: project evaluation; quality model, quality in use, external metrics, and project leaders.